Restorative Justice In The Perspective Of Contemporary Procedural Law - Fatihah, Nurul (Universitas Pahlawan Tuanku Tambusai, 2024)
The retributive approach to criminal procedural legislation in Indonesia is formal and controlled by the legal system, which is at odds with the concepts of restorative justice, as discussed in this paper. Instead of punishing wrongdoers, victims, and society as a whole may find healing and rehabilitation via restorative justice's humanistic approach. But this method is still not often used, particularly when dealing with major offenses that are heavily controlled by formal law, like murder and corruption. Both victims and offenders' emotional preparedness and a lack of community support, which is crucial for healing, are the primary obstacles to restorative justice's adoption in Indonesia. In order to determine how far restorative justice may go in Indonesia's official criminal justice system, this research use normative legal methodologies by reviewing relevant legislation and legal theories. According to the study's findings, restorative justice can't be put into practice without sweeping changes to regulations, stronger police enforcement, and active community involvement.